Comparison of Nocturia Response to Desmopressin Treatment between Patients with Normal and High Nocturnal Bladder Capacity Index - Tine Hajdinjak; Jurij Leskovar (The Scientific World Journal)
Objective. To compare efficacy of desmopressin for treatment of nocturia between patients with normal and high nocturnal bladder capacity index (NBCi). Methods. Retrospective analysis of adult patients treated with desmopressin for nocturia. Patients were analyzed according to high or normal NBCi value before treatment. Results. 55 patients were identified, aged 49–84, 47 males, 8 females, who started desmopressin 0.2 mg nocte between 2009 and 2011. Two groups (N: normal and H: high NBCi) were similar regarding number, gender, age, 24 h urine volume, and nocturnal urine volume. On treatment, nocturnal volume decreased by mean of 364 mL. Number of nightly voids decreased in N group from 3.11 to 1.50, in H from 3.96 to 1.44. Nocturnal polyuria and nocturia indices also decreased significantly. NBCi remained the same in N group (0.56 on therapy) and in H group decreased to mean 0.63. All on-treatment values were statistically similar in N and H groups. Pretreatment differences were abolished with treatment. NBCi was significantly correlated to nocturia reduction—larger reduction was observed in patients with higher NBCi. In 8/55 patients, hyponatremia was detected, but without clinical consequences. Conclusions. The results indicate that the effectiveness of desmopressin on nocturia is not dependent upon the patient's pretreatment NBCi.